Amino‐terminal fragments of laminin γ2 chain retract vascular endothelial cells and increase vascular permeability. Issue 2 (7th January 2014) - Sato, Hiroki; Oyanagi, Jun; Komiya, Eriko; Ogawa, Takashi; Higashi, Shouichi; Miyazaki, Kaoru
Abstract : Laminin γ2 (Lmγ2) chain, a subunit of laminin‐332, is a typical molecular marker of invading cancer cells, and its expression correlates with poor prognosis of cancer patients. It was previously found that forced expression of Lmγ2 in cancer cells promotes their invasive growth in nude mice. However, the mechanism of the tumor‐promoting activity of Lmγ2 remains unknown. Here we investigated the interaction between Lmγ2 and vascular endothelial cells. When treated with an N‐terminal proteolytic fragment of γ2 (γ2pf), HUVECs became markedly retracted or shrunken. The overexpression of Lmγ2 or treatment with γ2pf stimulated T‐24 bladder carcinoma cells to invade into the HUVEC monolayer and enhanced their transendothelial migration in vitro . Moreover, γ2pf increased endothelial permeability in vitro and in vivo . As the possible mechanisms, γ2pf activated ERK and p38 MAPK but inactivated Akt in HUVECs. Such effects of γ2pf led to prominent actin stress fiber formation in HUVECs, which was blocked by a ROCK inhibitor. In addition, γ2pf induced delocalization of VE‐cadherin and β‐catenin from the intercellular junction. As possible receptors, γ2pf interacted with heparan sulfate proteoglycans on the surface of HUVECs. Moreover, we localized the active site of γ2pf to the N‐terminal epidermal growth factor‐like repeat. These data suggest that the interaction between γ2pf and heparan sulfate proteoglycans induces cytoskeletal changes of endothelial cells, leading to the loss of endothelial barrier function and the enhanced transendothelial migration of cancer cells. These activities of Lmγ2 seem to support the aberrant growth of cancer cells. Abstract : An N‐terminal fragment of the laminin gamma2 chain retracts vascular endothelial cells by inducing delocalization of VE‐cadherin.